Outcomes in women undergoing robotic‐assisted laparoscopic hysterectomy compared to conventional laparoscopic hysterectomy at a tertiary hospital in Western Australia. (23rd November 2017) - Rajadurai, Vinita A.; Tan, Jason; Salfinger, Stuart G.; Cohen, Paul A.
Abstract : Background: Robotic‐assisted laparoscopic hysterectomy (RALH) is associated with improved outcomes compared to open surgery in patients with endometrial cancer but data are conflicting when comparing RALH to conventional total laparoscopic hysterectomy (TLH). In October 2014, a RALH program was established in Perth, Western Australia. Aim: To compare outcomes in patients undergoing RALH with a matched cohort undergoing TLH. Materials and methods: A retrospective matched cohort study compared outcomes in 45 patients who underwent RALH with 45 controls who were patients treated with TLH. Results: Mean operating time was longer in the RALH group compared to controls (75.42 min vs 53.18 min, mean difference 22.24 min, P < 0.001, 95% Cl, 11.07–33.42). No differences were observed in mean pain scores (RALH 1.47 vs TLH 1.84 P = 0.31), mean parenteral and oral opioid use (RALH 14.3 mg and 42.4 mg vs TLH 17.5 mg and 52.57 mg, P = 0.42 and 0.42, respectively), and mean length of stay (RALH 1.51 vs TLH 1.67 days, P = 0.49). Two patients in the RALH group and one patient in the TLH group sustained iatrogenic bladder injuries ( P = 0.62). Conclusion: The establishment of the RALH program at our institution appeared to be associated with equivalent morbidity, post‐operative pain, opioid use and length of stay compared to conventional laparoscopy. A surgical learning curve for RALH was observed. Well‐designed prospective studies are needed to further evaluate short‐ and long‐term patient function, morbidity, quality of life and oncologic outcomes.